Interoceptive Awareness Skills for Emotion Regulation: Theory and Approach of Mindful Awareness in Body-Oriented Therapy (MABT) - Price, Cynthia J.; Hooven, Carole (Frontiers in Psychology, 2018)
Emotion regulation involves a coherent relationship with the self, specifically effective communication between body, mind and feelings. Effective emotion regulation involves the ability to accurately detect and evaluate cues related to physiological reactions to stressful events, accompanied by appropriate regulation strategies that temper and influence the emotional response. There is compelling evidence demonstrating links between poor or disrupted awareness of sensory information, or interoceptive awareness, and difficulties with emotion regulation. This paper presents a framework, based on psychological and neurobiological research, for understanding how interoceptive awareness facilitates regulation and an integrated sense of self, and thus contributes to health and wellbeing. A mind-body therapeutic approach called Mindful Awareness in Body-oriented Therapy (MABT), uniquely designed to teach fundamental skills of interoceptive awareness, is described. MABT develops the distinct interoceptive awareness capacities of identifying, accessing, and appraising internal bodily signals that are identified in physiological models as the critical components of interoception for emotion regulation. The explanatory model is that the development of these key interoceptive capacities improves sensory (physical and emotional) awareness, reduces distress, and improves regulation. Strategies for teaching and learning interoceptive awareness are not well developed in mindfulness or psychotherapeutic approaches, particularly important for people who may have difficulty attending to interoceptive awareness due to stress, chronic pain or trauma. To address this issue, MABT provides an individualized protocol for scaffolding interoceptive awareness through a combination of psychoeducation and somatic approaches explicitly addressing difficulties with interoceptive processing. Clinical vignettes are included to provide exemplars of this approach and to highlight key components of the therapeutic process. Results from research are also included to highlight the acceptability, safety, health outcomes, and possible mechanisms underlying the MABT approach.